Role of Cationic Oxidation States to Enhance the Electroactive β‐Phase of Poly(vinylidene Fluoride) and its Energy Harvesting Performance. Issue 22 (28th August 2018) - Ganesan, Kausalya; Alluri, Nagamalleswara R.; Raj, Nirmal Prashanth M. J.; Chandrasekhar, A.; Kim, S.‐J.
Abstract: Transparent, flexible and efficient ferroelectric composite films were fabricated by a simple ultrasonication approach followed by thermal treatment. The enhanced electroactive β‐phase and stabilization of the ferroelectric poly(vinylidene fluoride) (PVDF) polymer were analyzed by the substitution of various cations with different oxidation states (Li 1+, Al 3+ ) as fillers. The electroactive β‐phase was obtained due to the stretching of −CH2 −/−CF2 − molecular chains, stress‐induced effects during the sonication process and the interfacial interaction between the molecular chains and the surface charge of foreign elements. Further, a flexible ferroelectric nanogenerator was implemented and subjected to harness the waste biomechanical energy. The PVDF/Al 3+ composite film‐based device gave the maximum amount of voltage and current of 189 V and 0.97 μA respectively at 2 N force. This high electrical output is caused by the electrostatic interaction between electronegative fluorine atoms and the surface active, positive charged ions of the fillers. The obtained maximum instantaneous power density of the FF‐CNG device at 20 MΩ load resistance is 1.92 mW/m 2 . The generated output is used to power up commercial light‐emitting diodes and display devices without using storage components. The proposed approach for enhancing the throughput of ferroelectric polymers can pave the way to develop new smart composite films for efficient energy conversion. Abstract : Piezoelectric films of poly(vinylidene fluoride) (PVDF) are fabricated by ultrasonication followed by thermal treatment. The electroactive β‐phase is obtained due to −CH2 −/−CF2 − chain stretching, effects during sonication and interfacial interactions between molecular chains and the charge of substituted cations. Substitution of cations is improving the stabilisation of the electroactive phase by increasing the interfacial polarization of PVDF.